Globalization, institutions & governance - Caporaso, James A., 1941-; Madeira, Mary Anne. (London ; Thousand Oaks, Calif. : Sage, 2012)
"The study of international relations now goes well beyond state-to-state politics and even regional politics. Technological forces are working their effects on the world as a whole, bringing state and non-state actors into contact with one another. Globalization, Institutions and Governance provides students with a sophisticated and engaging exploration of the often differing impacts of these technological forces and the wider implications of globalization for theories of global governance and the role of international institutions"--Publisher's website.
Introduction -- Theories of global political economy -- Domestic responses to pressures of globalization -- Globalization and governance -- International institutions and the global economy -- Winners and losers of globalization -- Conclusion.
Includes bibliographical references (p. [174]-184) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Globalization; Globalization -- Political aspects; Globalization -- Economic aspects; Corporate governance; International economic relations; Electronic books